2001
DOI: 10.1161/01.hyp.37.2.787
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptor Affects AP-1 and Nuclear Factor-κB Activation in Angiotensin II–Induced Cardiac Injury

Abstract: Abstract-Aldosterone is implicated in cardiac hypertrophy and fibrosis. We tested the role of the mineralocorticoid receptor in a model of angiotensin II-induced cardiac injury. We administered spironolactone (SPIRO; 20 mg · kg, valsartan (VAL; 10 mg · kg Ϫ1 · d Ϫ1 ), or vehicle to rats double transgenic for the human renin and angiotensinogen genes (dTGR). We investigated basic fibroblast growth factor (bFGF), platelet-derived growth factor, transforming growth factor-␤ 1 , and the transcription factors AP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(141 citation statements)
references
References 40 publications
8
131
0
2
Order By: Relevance
“…Earlier, we studied a similar rat model using Spi. 21 In that study, we also found that Spi ameliorated cardiac hypertrophy and fibrosis, largely independently of blood pressure. Taken together, these studies support the notion that Ald induces cardiac fibrosis independently of other renin-angiotensin system components.…”
Section: Mazak Et Al Angiotensin II and Aldosterone 2797mentioning
confidence: 60%
“…Earlier, we studied a similar rat model using Spi. 21 In that study, we also found that Spi ameliorated cardiac hypertrophy and fibrosis, largely independently of blood pressure. Taken together, these studies support the notion that Ald induces cardiac fibrosis independently of other renin-angiotensin system components.…”
Section: Mazak Et Al Angiotensin II and Aldosterone 2797mentioning
confidence: 60%
“…27 Recent reports on MR inhibitors demonstrated that NF-B activation was suppressed by administration of an MR inhibitor spironolactone to rats treated with continuous infusion of aldosterone 25 or to double transgenic rats harboring human renin and angiotensinogen genes (dTGR). 28 These findings suggest the possibilities that activation of NF-B-mediated induction of iNOS from the oxidative stress-LOX-1 pathway plays important roles in the pathology of heart failure and that eplerenone suppresses iNOS induction via suppressing NF-B activation through oxidative stress-LOX-1, which may lead to improvements in cardiac function and remodeling.…”
Section: Discussionmentioning
confidence: 77%
“…This mechanism has been postulated for the aldosteronedependent induction of epidermal growth factor receptor expression 41 and for the cardiac actions of aldosterone. 42 Numerous potential AP1 binding sites were identified in the promoter region of the human, mouse, and rat AT2R genes. 43,44 Clarification of these or other potential mechanisms mediating AT2R mRNA abundance changes will need further studies.…”
Section: Discussionmentioning
confidence: 99%